Braiding sweetgrass families: a transmedia project on parenting in Blackfoot Territory. (1st March 2020) - Newberry, Jan; Pace-Crosschild, Tanya
Abstract : This photo-essay shares images from a collaborative project between a local university and an agency devoted to Indigenous children and their families in southern Alberta, Canada. The original project used photo-elicitation to identify local childrearing values, but the project ultimately became a transmedia one. Here, we use images to elaborate on the sweetgrass braid as a metaphor for the braided character of parenting across the many divides, historic and contemporary, that cross Blackfoot Territory.